Utilitarian and ideological determinants of attitudes toward immigration: Germany before and after the "refugee crisis" - Heinz Welsch (University of Oldenburg, Department of Economics, 2019)
Previous studies on the determinants of attitudes toward immigration can be classified into those that take a utilitarian perspective, focusing on individuals' perceptions of real-world impacts of immigration, and those that look at immigration attitudes from the point of view of ideological orientation, focusing on broad political norms and values. While utilitarian and ideological determinants have largely been studied separately, the present paper sets out to disentangle their role, placing an emphasis on possible interconnections between them. Specifically, the paper studies whether and to what extent individuals' perception of the impacts of immigration is related to their ideological orientation, implying an indirect channel through which ideology may shape attitudes toward immigration policies. Focusing on Germany before and after the so-called refugee crisis of 2015, it is found that while perceptions of economic and cultural impacts are more important than ideological position, perceptions of impacts increasingly depend on ideology. Ideology-dependence of perceptions is stronger with respect to cultural than with respect to economic impacts. While the importance of perceived economic impacts has decreased, cultural impacts have become the dominant concern after the crisis. Ideological position is more important with respect to immigrants of a different race or ethnic group than the majority and immigrants from poorer countries outside Europe than with respect to immigrants of the same race or ethnic group. The relationship between ideology and immigration attitudes rests mainly on the identity/homogeneity domain of ideological position rather than the equity/solidarity domain.
Keywords: F22; I31; J15; O15; Z13; 330; immigration; attitude; utilitarianism; left-right scale; equity; identity